The influence of government spending in the education, health and infrastructure sectors on economic growth and the human development index in North Sumatra province for the period 2015–2024 - Suci Syahrovani Nasution (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
This study aims to analyze the effect of government spending on the education, health, and infrastructure sectors on economic growth and the Human Development Index (HDI) in North Sumatra Province during the 2015–2024 period. The main issue examined is the extent to which the effectiveness of public budget allocation is able to encourage economic development while improving human quality. This study uses a quantitative approach with a multiple linear regression method processed using EViews 10 software, and utilizes secondary data sourced from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK). The results show that government spending on the health and infrastructure sectors has a significant effect on economic growth and the HDI, while spending on the education sector shows a positive but not significant effect in the short term. Simultaneously, the three expenditure sectors have a significant effect on both development indicators with a strong coefficient of determination value, namely above 75%. This finding emphasizes the importance of balanced budget allocation between the social and physical sectors to encourage inclusive and sustainable regional development.